2017
DOI: 10.1002/cnma.201700196
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Magnetic Anisotropy Induced by the Combined Control of Size, Shape and Organization of NiFe Prussian Blue Analog Nanoparticles in an Ordered Mesoporous Silica Monolith

Abstract: Integration of coordination polymers and metal–organic frameworks into real applications requires a processing step at the nanoscale. However, their synthesis in the form of nanoparticles with controlled size, shape and organization remains a challenge faced by diverse scientific communities. Ordered mesoporous silica monolith with 2D‐hexagonal structure of the mesopores is used to form ferromagnetic NiFe Prussian blue analog (PBA) nanoparticles with anisotropic shape. The PBA nanowires formed within the nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The monolith contains 2.7% by weight of CoFe PBA. We already showed that the CoFe PBA Nps exhibit the well‐known face‐centered cubic structure of PBAs (Figure S1); they are single‐crystalline and their diameter is determined by the diameter of the pores ,. The PBA Nps can be seen as dots (transverse section) on the TEM image of MonoPBACoFe (Figure a).…”
Section: Assembly Of Cofe Pba Nanocrystalsmentioning
confidence: 80%
See 1 more Smart Citation
“…The monolith contains 2.7% by weight of CoFe PBA. We already showed that the CoFe PBA Nps exhibit the well‐known face‐centered cubic structure of PBAs (Figure S1); they are single‐crystalline and their diameter is determined by the diameter of the pores ,. The PBA Nps can be seen as dots (transverse section) on the TEM image of MonoPBACoFe (Figure a).…”
Section: Assembly Of Cofe Pba Nanocrystalsmentioning
confidence: 80%
“…They are therefore appealing precursors for the preparation of mixed metal oxides and metal alloys with well‐tuned magnetic properties. Combined with the mastering of the synthesis of mesoporous silica monoliths by surfactant‐assisted sol‐gel chemistry, which enables the production of macroscopic silica blocks exhibiting 2D‐hexagonal structure of the mesopores in single orientation domains with typical volume of 0.2 mm 3 , the mastering of confined coordination chemistry enables the formation of single‐crystalline PBA nanoparticles fully confined in the cylindrical pores ,. The ordered porosity of the silica induces an anisotropic spatial organization of the functional nanoparticles along the pores axis and set their size, shape and aggregation state.…”
Section: Introductionmentioning
confidence: 99%
“…The main differences between the magnetic properties of the three first compounds and RbNanoCoFe* can be explained in terms of different inter-particle interactions. It is worth recalling here that the particles having the same size as the diameter of the cylindrical pores can aggregate forming chains inside the channels [40], which are separated from each other by 4 nm walls. First, the T max value for RbNanoCoFe* (8.3 K) is significantly higher than the T max value for HNanoCoFe*, HNanoCoFe and KNanoCoFe (5.4 K, 5.4 K and 4.6 K, respectively) and it is usually assumed that T max shifts to higher temperature with increasing inter-particle interactions [41][42][43][44].…”
Section: Resultsmentioning
confidence: 99%
“…As a possible solution, the use of macroscopic ordered monoliths can be envisioned. [3] In that case, the sol-gel process and in particular the drying procedure have to be well controlled to ensure that the ordered silica network does not collapse and to avoid the formation of cracks. [4,5] Regardless of the silica morphology, the porosity has to be loaded with the precursor and for that purpose an impregnation with an aqueous solution containing metal salts is typically used.…”
Section: Introductionmentioning
confidence: 99%
“…[21] For the assembly of NiFe PBA nanoparticles within an ordered silica monolith, differences in the coercive field could be observed depending on the orientation of the pores in the applied magnetic field. [3] Another study looked at CoFe2O4 nanoparticles dispersed or not in a dense silica matrix. [22] The dispersion in silica leads to the formation of non-interacting superparamagnetic nanoparticles, whereas the non-embedded particles were strongly interacting.…”
Section: Introductionmentioning
confidence: 99%